2023
DOI: 10.1186/s40942-023-00443-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathomechanisms in central serous chorioretinopathy: A recent update

Abstract: Background Central serous chorioretinopathy (CSCR) is a potentially blinding choroidal disease. Despite decades of research, the pathological mechanisms of CSCR are still poorly understood. In recent years, there has been a strong emphasis on choroidal dysfunction as a primary cause of CSCR. Main Body The concept of the pachychoroid disease spectrum and pachychoroid-driven processes are central to current theories regarding the pathophysiological u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Central serous chorioretinopathy belongs to the pachychoroid disease spectrum. Much research work has been conducted to elucidate the exact pathophysiology of pachychoroid and CSCR, with some theories including venous congestion, mineralocorticoid receptor (MR) activation, inflammatory processes, and systemic conditions with hemodynamics alterations 12 . Recent studies have demonstrated an increased vulnerability of choroidal blood flow to vascular variations in patients with CSCR 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Central serous chorioretinopathy belongs to the pachychoroid disease spectrum. Much research work has been conducted to elucidate the exact pathophysiology of pachychoroid and CSCR, with some theories including venous congestion, mineralocorticoid receptor (MR) activation, inflammatory processes, and systemic conditions with hemodynamics alterations 12 . Recent studies have demonstrated an increased vulnerability of choroidal blood flow to vascular variations in patients with CSCR 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The alteration is primarily localized in the macular area, with fluid accumulating in the subretinal space. Several explanations concerning the disease's pathophysiology have been offered, two of which are accepted: choroidal dysfunction and pigment epithelial dysfunction [ 5 , 16 ]. Although the exact mechanism of the disease has not been determined, radiographic studies have revealed that the predominant alteration in the CSCR eye is due to increased permeability, which results in systemic fluid leakage from choroidal capillaries into the subretinal area [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effektivität der Subthreshold-Micropulse-Laser-Therapie bei der Chorioretinopathia centralis serosa Background/Introduction Central serous chorioretinopathy (CSCR) is a disease of the pachychoroid spectrum. The currently most accepted pathophysiological mechanism includes primary choroidal dysfunction, possibly due to venous congestion, inflammation, aberrant steroid metabolism, and genetic factors [1,2]. Besides choroidal dysfunction, acute CSCR is defined by subretinal fluid (SRF) accumulation resulting from one or more leakage points due to a micro-tear in the retinal pigment epithelium (RPE) [3].…”
Section: Efficacy Of Subthreshold Micropulse Laser For Central Serous...mentioning
confidence: 99%